2021
DOI: 10.21203/rs.3.rs-199769/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Photodissociation of CF3CHO provides a new source of CHF3 (HFC-23) in the atmosphere: implications for new refrigerants.

Abstract: Throughout the last century, chlorofluorocarbons (CFCs) and hydrochlorofluorocarbons (HCFCs) were the most widely used refrigerants. However, it was discovered that they released reactive chlorine in the upper atmosphere causing the hole in the ozone layer and they were phased out by the 1987 Montreal Protocol [1]. They were replaced by hydrofluorocarbons (HFCs), which contain no chlorine and do not damage the ozone layer. However, HFCs are potent greenhouse gases and they were phased out in a 2016 amendment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…It has been recently argued that photolysis of this molecule leads to the formation of CHF 3 , one of the most potent greenhouse gases. While the photochemistry of CF 3 COH and CF 3 COCl might be expected to be similar, the quantitative differences between these two atmospheric molecules lead to a photochemical instability of the C–Cl bond even at long wavelengths, meaning that the analogical CF 3 Cl product only appears as a very minor product that could not be detected in our work …”
Section: Wavelength Dependence Of the Cf3cocl Photochemistrymentioning
confidence: 99%
“…It has been recently argued that photolysis of this molecule leads to the formation of CHF 3 , one of the most potent greenhouse gases. While the photochemistry of CF 3 COH and CF 3 COCl might be expected to be similar, the quantitative differences between these two atmospheric molecules lead to a photochemical instability of the C–Cl bond even at long wavelengths, meaning that the analogical CF 3 Cl product only appears as a very minor product that could not be detected in our work …”
Section: Wavelength Dependence Of the Cf3cocl Photochemistrymentioning
confidence: 99%
“…被认定为轻微可燃制冷剂 [78]- [80] ,R1234yf 溶于水可能形成三氟乙酸等 [81] ;甚至,在最新的 研究中,有学者提出 HFO 类制冷剂在大气中会分解产生 CF3CHO(三氟乙醛),最终分解 产生 CHF3(HFC-23),HFC-23 是一种强温室效应气体,可能最终导致 HFO 类制冷剂的 GWP 值进行重新评估 [82] 。另外,受限于美国公司的专利保护,R1234yf 高昂的价格 [83] 也是 目前限制其在国内广泛普及的主要问题。 [86] 。在此背景下,虽然很多学者研究并优化了 R290 在车辆制冷系 统内的泄露情况 [87] ,或主张采用多元混合物制冷剂的方式降低 R290 的当量充注量 [88] ,但可 燃性一直是 R290 制冷剂最大的安全隐患。 Since the signing and implementation of the Kigali Amendment to the Montreal Protocol, reducing equivalent carbon emissions and effectively slowing down global warming has become the most appealing topic in various industries worldwide. The total carbon emissions of the transportation industry, which is one of the most important sources of carbon emissions, account for approximately 30% of the total value of the economy and society.…”
Section: 制冷剂应用现状unclassified
“…The previous studies reported that the use of HFO-1234yf instead of HFC-134a will likely result in enhanced and more localized TFA deposition. Trifluoroacetaldehyde (CF 3 CHO) is the main degradation product of HFO-1234ze . CF 3 CHO can be partially degraded to TFA , and is mainly removed by photolysis. , Researchers have discrepancies on the yield of HFC-23 (CHF 3 ) production by photolysis of CF 3 CHO. HFC-23 has the highest 100-year global warming potential (GWP) of 12 690 among HFCs with an atmospheric lifetime of 228 years . The formation of HFC-23 could lead to a secondary contribution to radiative forcing of parent HFOs …”
Section: Introductionmentioning
confidence: 99%